Coping with salt stress-interaction of halotolerant bacteria in crop plants: A mini review - Ramasamy, Kesava Priyan; Mahawar, Lovely (Frontiers in Microbiology, 2023)
Salinity is one of the major environmental abiotic stress that limits the growth and yield of crop plants worldwide. Understanding the importance of several adaptive mechanisms in plants towards salt stress is crucial to increase agricultural productivity. Plant resilience towards salinity stress is improved by cohabiting with diverse microorganisms, especially bacteria. In the last decades, increased attention has focused on bacterial communities for promoting plant growth and plant fitness. The biotechnological applications of salt-tolerant plant growth-promoting rhizobacteria (PGPR) gained vast interest for their numerous metabolites. This review provides novel insights into the importance of halotolerant bacteria associated with crop plants in enhancing plant tolerance towards salinity stress. Furthermore, we highlight several challenges of using HT-PGPR in agricultural field and possible solutions to overcome those challenges for future sustainable agriculture development.